2015
DOI: 10.1039/c5cp03729h
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical spectroscopic studies on chemical and electronic structures of arginylglycine

Abstract: The energy differences between canonical and zwitterionic isomers of arginylglycine (ArgGly) at the CCSD/aug-cc-pVDZ level are too small (less than 1 kcal mol(-1)) to determine the dominant form in the gas phase from the energetic point of view. First-principles simulations have been performed for near-edge X-ray absorption fine-structure (NEXAFS) spectra and X-ray photoelectron spectra (XPS) at C, N and O K-edges, as well as for infrared (IR) spectra of neutral ArgGly. Noticeable spectral differences were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Briefly speaking, the whole molecule was divided into two parts by the amide bond: the first one is the main-chain part, including the carboxyl group, the amino group and four methylene groups and the second one is the side-chain part, mainly including the amide bond and the pyrroline ring. The rotational details are similar to our previous work on several large flexible molecules. , …”
Section: Computational Detailssupporting
confidence: 58%
See 1 more Smart Citation
“…Briefly speaking, the whole molecule was divided into two parts by the amide bond: the first one is the main-chain part, including the carboxyl group, the amino group and four methylene groups and the second one is the side-chain part, mainly including the amide bond and the pyrroline ring. The rotational details are similar to our previous work on several large flexible molecules. , …”
Section: Computational Detailssupporting
confidence: 58%
“…The latter vibration red-shifted ca. 52 cm −1 compared with that of several similar molecules, 18,36,55 mainly due to the strong interaction between the carboxyl group and the amide bond in Pyl. For its deprotonated form, the peaks around 700−900 cm −1 are similar to that of the canonical form.…”
Section: Resultsmentioning
confidence: 90%
“…It is found that the global minimum is still the zwitterionic conformer R z1 . Furthermore, it is interesting to find that the energy differences between the zwitterionic and canonical forms become larger with the improved theoretical methods (more than 3.18 and 5.00 kcal mol –1 ), which is opposite to the situation on dipeptide arginylglycine . It seems that with the improvement in the computational accuracy, the identification of the dominant form from the energetic point of view becomes possible for the hydrated molecules.…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, it is interesting to find that the energy differences between the zwitterionic and canonical forms become larger with the improved theoretical methods (more than 3.18 and 5.00 kcal mol −1 ), which is opposite to the situation on dipeptide arginylglycine. 12 It seems that with the improvement in the computational accuracy, the identification of the dominant form from the energetic point of view becomes possible for the hydrated molecules. Therefore, we believed that, at least for this hydrated molecule, calculations at the CCSD/6-311++G(d,p) are good enough to give reliable theoretical values.…”
mentioning
confidence: 99%
See 1 more Smart Citation